SOME ISSUES OF LEGAL REGULATION IN THE FIELD OF COPYRIGHT - Аверкова, М. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
In this article the author investigates the public relations connected with emergence of objects of copyright, functioning of subjective copyrights and their legal protection in the international and national private law.